Overshoot proofing adaptation policies and plans - Yesil,B; Theokritoff,E; Pringle,P; Menke,I; Schleussner,C-F (2023)
With 1.2°C current global warming, it becomes increasingly important to think about overshoot and what this would imply for adaptation. In the face of increasing impacts, more and more thresholds and limits to adaptation will be reached – but if global warming levels are brought down again through the deployment of negative emission technologies, what does this imply for adaptation?Here, we present a methodology which aims to provide concrete entry points for integrating overshoot risks into adaptation planning, with the objective of strengthening resilience, reducing vulnerability and avoiding maladaptation. We explore concepts such as impact (un)avoidability and (ir)reversibility, key elements of long-term adaptation planning. Ultimately, we aim to develop a step-based approach allowing adaptation planners to formulate and review adaptation policies adequately integrating the concept of overshoot and its implications.